10-Year survey on serum antibody positivity rates and titers for measles and rubella in healthcare workers; an observational study at a Japanese university hospital. Issue 9 (September 2021) - Yoshioka, Nori; Deguchi, Matsuo; Hagiya, Hideharu; Kagita, Masanori; Tsukamoto, Hiroko; Takao, Miyuki; Yoshida, Hisao; Hamaguchi, Shigeto; Maeda, Ikuhiro; Hidaka, Yoh; Tomono, Kazunori
Abstract: Background: We evaluated the effect of the two-dose vaccination strategy, which has been a widely adopted as childhood routine schedule worldwide to acquire herd immunity, on healthcare workers (HCWs) in Japan. Methods: Between 2010 and 2019, antibody titers for measles and rubella were measured annually among newly employed HCWs at Osaka University Hospital, Japan, using Enzygnost® assays (Siemens Healthcare Diagnostics Co. Ltd., Marburg, Germany). The data were categorized by age to compare the antibody positivity rates and antibody titers among no-vaccine, single-dose, and two-dose groups. Results: Over the 10-year period, the annual antibody positivity rates for measles and rubella were 84.0%–95.3% and 90.0%–94.5%, respectively, without any particular trend. The antibody titers for measles (median [interquartile range]: 8.4 [3.9, 20] vs. 6.1 [3.5, 12]) and rubella (11 [5.5, 20] vs. 6 [3.7, 11]) were statistically lower ( p  < 0.001) in the two-dose generation than in the single-dose generation. Discussion: A shift from single-dose to two-dose vaccination did not yield an increase in antibody positivity rates for both measles and rubella among HCWs. Notably, antibody titers were significantly lower in the two-dose generation. Conclusion: Despite several limitations, our data suggests a paradoxical vulnerability in young HCWs who received the two-dose vaccination in a view of sero-positivity rates.